2021
DOI: 10.3390/pharmaceutics13081183
|View full text |Cite
|
Sign up to set email alerts
|

Solid Lipid Nanoparticles (SLNs): An Advanced Drug Delivery System Targeting Brain through BBB

Abstract: The blood–brain barrier (BBB) plays a vital role in the protection and maintenance of homeostasis in the brain. In this way, it is an interesting target as an interface for various types of drug delivery, specifically in the context of the treatment of several neuropathological conditions where the therapeutic agents cannot cross the BBB. Drug toxicity and on-target specificity are among some of the limitations associated with current neurotherapeutics. In recent years, advances in nanodrug delivery have enabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
70
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(70 citation statements)
references
References 251 publications
(201 reference statements)
0
70
0
Order By: Relevance
“…Microbial manipulation: microbiota transplant in GI disorders (269)(270)(271)(272) Microbial manipulation: microbiota transplant in neurodegenerative disorders (273)(274)(275)(276) Natural products in neurodegenerative disorders (277,278) Natural products in GI disorders (279,280) Dietary fibers in GI disorders (281) Nanotechnology and nanotheranostic approach in neurodegenerative disorders (282)(283)(284) Oxidized phospholipidis (285,286) SCFAs in GI inflammatory disorders (287)(288)(289) CD36 in Alzheimer's disease (290) Firmicutes Clostridiaceae Decreased in IBS (291) Increased in IBD (292,293) Increased in CD (293) Increased in Parkinson's disease (284,294) Increased in autism spectrum disorder (256,257) Decreased in bipolar disorder (258) Increases mucosal 5-HT and EC cells and decreased SERT expression (295) Correlated with increased levels of serotonin (263) Increases SERT expression (296) Lachnospiraceae Decreased in IBS (291) Decreased in IBD (293,297) Decreased in UC and CD (298) Not modified in CD (252) Increased in UC (252) Decreased in Parkinson's disease (259,…”
Section: -Ht Alterations Therapeutic Approachmentioning
confidence: 99%
“…Microbial manipulation: microbiota transplant in GI disorders (269)(270)(271)(272) Microbial manipulation: microbiota transplant in neurodegenerative disorders (273)(274)(275)(276) Natural products in neurodegenerative disorders (277,278) Natural products in GI disorders (279,280) Dietary fibers in GI disorders (281) Nanotechnology and nanotheranostic approach in neurodegenerative disorders (282)(283)(284) Oxidized phospholipidis (285,286) SCFAs in GI inflammatory disorders (287)(288)(289) CD36 in Alzheimer's disease (290) Firmicutes Clostridiaceae Decreased in IBS (291) Increased in IBD (292,293) Increased in CD (293) Increased in Parkinson's disease (284,294) Increased in autism spectrum disorder (256,257) Decreased in bipolar disorder (258) Increases mucosal 5-HT and EC cells and decreased SERT expression (295) Correlated with increased levels of serotonin (263) Increases SERT expression (296) Lachnospiraceae Decreased in IBS (291) Decreased in IBD (293,297) Decreased in UC and CD (298) Not modified in CD (252) Increased in UC (252) Decreased in Parkinson's disease (259,…”
Section: -Ht Alterations Therapeutic Approachmentioning
confidence: 99%
“…The in vivo study confirmed the ability of the surface-tailored emulsomes to achieve improved VNP brain delivery compared to either oral market product or corresponding non-tailored formulations. PEG is able to target the brain endothelial cell receptors via induction of receptor-mediated transcytosis (Qiao et al., 2012 ; Pulgar, 2018 ), while SA targets the brain via the interaction with the negative charges existing on the BBB (Bors & Erdő, 2019 ; Satapathy et al., 2021 ), resulting in adsorptive-mediated endocytosis.…”
Section: Resultsmentioning
confidence: 99%
“…The decision to give 3 mg of melatonin tablet every three hours between 24 hours and 48 hours, i.e., during the second day of the investigation, was to maintain the supraphysiological concen-tration of melatonin in blood plasma in order to see if it would affect the sleep. Melatonin per os has good tolerability and scarce evidence of side effects [9,10].…”
Section: Discussionmentioning
confidence: 99%